KORELASI KEKUATAN GESER UNDRAINED TANAH LEMPUNG DARI UJI UNCONFINED COMPRESSION DAN UJI LABORATORY VANE SHEAR (STUDI PADA REMOLDED CLAY) - Wirya Ardana, Made Dodiek (Jurnal Ilmiah Teknik Sipil, 2012)
Strength test result of a soil investigation report often present a different value to the measured in-situ strength. It is become a constrain in using the value of soil parameter for foundation design on soft clay soil. Depends on the testing apparatus characteristic, test results from a different apparatus may differ even for a duplet samples. This may occur due to the different of procedure and the work mechanism of apparatus itself in determining the soil parameter. The goal of this study is to determine the correlation between test results of Su (undrained shear strength) of very soft to stiff clay obtain from Unconfined Compression Strength Test and Laboratory Vane Shear Test. The test results show a correlation of undrained shear strength values obtain from those two apparatus as follows : Su (vane) = 0.6214 . Su(uct) + 0.0028 atau Su (uct) = 1.5464. Su(vane) + 0.0049. Su obtain from vane shear test show a lower value of 37 % in comparisson with Unconfined Comporession values.
Keywords: Unconfined Compression Strentgh, Laboratory Vane Shear Test